Dilator Use After Vaginal Brachytherapy for Endometrial Cancer: A Randomized Feasibility and Adherence Study. Issue 3 (May 2018) - Hanlon, Alexandra; Small, William; Strauss, Jonathan; Lin, Lilie L.; Hanisch, Laura; Huang, Liming; Bai, Jinbing; Wells, Jessica; Bruner, Deborah Watkins
Abstract : Background: Vaginal brachytherapy, a common treatment of endometrial cancer, is associated with high rates of vaginal stenosis. Recommendations for vaginal dilator use to minimize stenosis generally include 3 times per week for approximately 10 minutes per use. However, adherence rates range widely and are generally well less than 50%. Objectives: The aims of this study were to assess feasibility of recruitment to a study of dilator use and test a theoretically driven enhanced educational program (EEP) to increase adherence. Methods: Eligibility included women treated with postoperative vaginal brachytherapy for stage I to IIIc endometrial cancer. Patients were randomized to either nurse-delivered standard institutional instruction or EEP. Results: Of eligible patients, 76% consented, 42 were randomized, and 69% completed the 6-month assessment. Mean age was 58.2 years; 48% were sexually active. There was no difference in adherence between arms. Overall, 20% and 8.3% were adherent to the prescribed use of 3 times per week, and 64% and 16% were adherent to use at least once per week at 6 weeks and 6 months, respectively. Adherence was greater among those motivated by vaginal health and having lower body mass index. Nonadherence was significantly higher among those who are college educated, in the EEP group, and with higher weight. Conclusions: Feasibility of recruitment into a study of vaginal dilator use was high. Adherence was low, and there was no difference between groups. Adherence to vaginal dilator use requires novel interventions to test. Implications for Practice: Nursing education that includes how dilators may maintain vaginal health may improve use because it was a motivator for adherence in this study.